On the Right Track: Servol's Early Childhood and Adolescent Development Programmes in Trinidad and Tobago - Guttman, Cynthia (UNESCO, 1994)
Servol was selected in 1994. The International year of the family, by UNESCO’s programme Education for All, Making it Work, as a showcase project because it works on all fronts to rebuild families and to give the disadvantaged self-esteem and hope for the future. This document describes the development of SERVOL, and its early childhood and adolescent development programmes. The introductory chapter provides an overview of Servol and its programmes. The second chapter describes the circumstances that led to the creation of Servol. The third chapter discusses its relevance in the current national context. The following chapters describe: 1) the Life Centres which put into action the idea of integrated education; 2) the Adolescent Development Programme (ADP) , which serves the emotional, psychological, educational, and vocational needs of adolescents; 3) the training of ADP instructors; 4) Fund Aid, the credit arm of Servol; 5) the Early Childhood Education Programme (ECEP); 6) The preschool teacher training course; 7) collaboration with the Government for funds; 8) funding from the private sector for the work of the life centres; 9) the relationship between the board of education and the community; and 10) replicating the Servol experience in the formal education system. The concluding chapter stresses the need for a responsive society in which education is supported by the community.
Keywords: Servol